2020
DOI: 10.1016/j.radcr.2020.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Primary hepatic neuroendocrine tumor: A rare entity

Abstract: Liver is the most common site for neuroendocrine metastasis. However, primary neuroendocrine tumor is a rare focal hepatic lesion with a better prognosis than hepatocellular carcinoma and other malignant hepatic lesions. We present a case of primary hepatic neuroendocrine tumor in a 38-year-old female patient with a radiological diagnosis of atypical focal hepatic lesion, and a confirmed diagnosis on histopathology. Few radiology features like predominant cystic component with absence of focal lesion at any ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…According to reports thus far, most PHNETs appeared in the form of a solid nodular lesion, and only a few cystic cases have been reported. [4][5][6] In the present case, however, it was a large multilocular cystic mass with septation, which led to the erroneous impression of hepatic mucinous cystadenoma or cystadenocarcinoma. A biopsy with an immunohistochemical examination can be helpful in diagnosis, but the cystic features of the mass made the authors hesitate to perform a biopsy.…”
Section: Discussionmentioning
confidence: 85%
“…According to reports thus far, most PHNETs appeared in the form of a solid nodular lesion, and only a few cystic cases have been reported. [4][5][6] In the present case, however, it was a large multilocular cystic mass with septation, which led to the erroneous impression of hepatic mucinous cystadenoma or cystadenocarcinoma. A biopsy with an immunohistochemical examination can be helpful in diagnosis, but the cystic features of the mass made the authors hesitate to perform a biopsy.…”
Section: Discussionmentioning
confidence: 85%
“… 5 Primary hepatic NETs account for approximately 0.3% of primary NETs. 6 They were first described in 1958 by Edmondson et al, and around 150 cases have been reported. 2 The origin is debated, with theories including ectopic pancreatic or adrenal cells, neuroendocrine tissue in the intrahepatic biliary epithelium, or chronic inflammation in the biliary tract causing metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…2 The origin is debated, with theories including ectopic pancreatic or adrenal cells, neuroendocrine tissue in the intrahepatic biliary epithelium, or chronic inflammation in the biliary tract causing metaplasia. 6 Primary hepatic NETs typically occur in patients aged 40-50 years, with no specific gender predominance, and no risk factors have been identified. 6 They can be functional, causing skin flushing, diarrhea, and abdominal pain due to hormone secretion (carcinoid syndrome), or be non-functional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, early diagnosis holds paramount importance in treatment decision-making and favorable prognosis for patients with PHNENs. The imaging manifestations of PHNENs reported in previous literature mainly consist of case reports ( 12 , 13 ) and lack systematic analysis. Hence, this study retrospectively analyzed clinical, pathological, and imaging data from 12 patients with PHNENs to enhance the accuracy of preoperative diagnosis.…”
Section: Introductionmentioning
confidence: 99%